Simultaneous functional photoacoustic and ultrasonic endoscopy of internal organs in vivo - Yang, Joon-Mo; Favazza, Christopher; Chen, Ruimin; Yao, Junjie; Cai, Xin; Maslov, Konstantin; Zhou, Qifa; Shung, K Kirk; Wang, Lihong V (Nature medicine, 2012)
Joon-Mo Yang and colleagues have developed a new endoscopic technique for the in vivo imaging of internal organs, combining endoscopic ultrasound and photoacoustic endoscopy in a single instrument. In addition to improved resolution, imaging depth, multimodal contrast, and distal-end scanning, the new hybrid imaging modality can also provide functional information such as hemoglobin concentration and blood oxygenation. Feasibility is shown in vivo by simultaneous photoacoustic endoscopy and endoscopic ultrasound imaging of the upper and lower gastrointestinal tracts of rats and rabbits. At present, clinicians routinely apply ultrasound endoscopy in a variety of interventional procedures that provide treatment solutions for diseased organs. Ultrasound endoscopy not only produces high-resolution images, but also is safe for clinical use and broadly applicable. However, for soft tissue imaging, its mechanical wave–based image contrast fundamentally limits its ability to provide physiologically specific functional information. By contrast, photoacoustic endoscopy possesses a unique combination of functional optical contrast and high spatial resolution at clinically relevant depths, ideal for imaging soft tissues. With these attributes, photoacoustic endoscopy can overcome the current limitations of ultrasound endoscopy. Moreover, the benefits of photoacoustic imaging do not come at the expense of existing ultrasound functions; photoacoustic endoscopy systems are inherently compatible with ultrasound imaging, thereby enabling multimodality imaging with complementary contrast. Here we present simultaneous photoacoustic and ultrasonic dual-mode endoscopy and show its ability to image internal organs in vivo , thus illustrating its potential clinical application.